(untitled) (Journal of the College of Basic Education, 2022)
In this search I am calculated theoretical model for attenuation of laser beam due to the scattering by the atmospheric particle (fog, mist, haze and dust)as a function of visual range (visibility). the theoretical results show that the laser wavelength in the Ultraviolet region 0.337 µm have attenuation more than Visible regions, 0.6328µm and near infrared region 1.06µm, also these result show that, in fog condition where visibility is less than 0.6km, the atmospheric attenuation of laser beam is independence of laser wavelength.